Preparation method of PEDOT: PSS composite copper grid flexible transparent conductive film

By using the PEDOT:PSS composite copper grid preparation method in the flexible transparent conductive film, the scarcity and fragility of the traditional ITO transparent conductive film is solved, and a high-performance and low-cost flexible transparent conductive film is achieved.

CN119694663AActive Publication Date: 2025-03-25HARBIN INST OF TECH AT WEIHAI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411856994.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Due to the scarcity and fragility of indium elements, the traditional ITO transparent conductive film has high preparation cost and is prone to cracks, resulting in a decrease in conductivity, making it difficult to meet the needs of the future market.

Method used

A high-performance transparent conductive film with PEDOT:PSS composite copper mesh is prepared by using PEDOT:PSS as the seed layer and conductive layer, combined with the copper mesh, and spin coating and magnetron sputtering technology are used to prepare high-performance transparent conductive films.

Benefits of technology

It achieves efficient conductivity and good flexibility, reduces preparation costs, simplifies the process flow, improves the smoothness and adhesion of the film, and avoids cracks and peeling problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694663A_ABST
    Figure CN119694663A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a PEDOT: PSS composite copper grid flexible transparent conductive film. The preparation method comprises the following steps: S1, cleaning a PET substrate; s2, a PEDOT: PSS solution is adjusted; s3, PEDOT: PSS is subjected to spin coating; s4, annealing: taking out the spin-coated PEDOT: PSS seed layer, and placing the spin-coated PEDOT: PSS seed layer in a vacuum drying oven for annealing to obtain a PEDOT: PSS film; s5, pre-sputtering of a target material; s6, a Cu film is sputtered on the PEDOT: PSS / PET substrate; and S7, preparing the copper grid composite conductive film. PEDOT: PSS / PET is adopted to replace PET to serve as the substrate, PEDOT: PSS serves as the seed layer, a good wetting effect can be provided for growth of the Cu layer, on the other hand, the Cu layer and the PEDOT: PSS layer can be compounded to give play to more excellent photoelectric performance by means of the conductivity of the PEDOT: PSS, the whole process is simple, complex operation is not needed, the laser direct writing speed is high, the pattern flexibility is high, and the method is suitable for large-scale production. And pattern parameters can be adjusted at will without being limited by masks, so that the preparation cost is relatively low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of transparent conductive films, and in particular relates to a method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film. Background Art

[0002] As smart electronics, photovoltaics and related new energy products move towards flexibility and transparency, flexible transparent conductive films are also moving forward driven by the growing market demand. At present, traditional ITO transparent conductive films still occupy most of the market, but due to the scarcity of indium, its preparation cost is high, and because ITO itself is relatively brittle, it is easy to crack, resulting in film damage and reduced conductivity. These properties restrict the large-scale use of ITO in the future market. Therefore, since the beginning of the last century, substitutes for ITO have been continuously developed. Currently, the market is optimistic about silver nanowires, metal grids and composite conductive films. Among them, metal grid flexible transparent conductive film refers to a transparent conductive metal grid film with periodic or random patterning on a flexible substrate. The metal mesh can adjust the size, line width, pattern and other parameters of the metal mesh according to the application requirements to adjust the optoelectronic performance. As a new generation of transparent conductive film, the metal grid has excellent comprehensive optoelectronic performance and good flexibility, becoming the most promising new generation of flexible transparent conductive film.

[0003] The manufacturing methods of metal mesh include photolithography, nanoimprint lithography, templated electrodeposition and imprint transfer (TEIT) process, and laser direct writing. Photolithography and nanoimprint lithography can control the mesh pattern with high precision, but the manufacture of high-performance metal mesh usually requires prefabricated high-precision templates, and the overall process is complicated and cumbersome, with high cost. Templated electrodeposition and imprint transfer (TEIT) process can obtain high-performance metal mesh with significant smoothness, but the TEIT process often involves complex multiple transfer and peeling procedures, which may lead to low cost effectiveness and poor repeatability in large-scale production.

[0004] The conductivity of the metal mesh transparent conductive film is mainly determined by the metal conductive layer. For the CuMesh conductive film, when PET is used as the substrate, the Cu film mainly grows in an island shape, so the photoelectric performance of the copper mesh prepared is poor.

[0005] Therefore, in view of the above technical problems, it is necessary to provide a method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film.

[0006] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film, which can solve the problems raised by the background technology.

[0008] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:

[0009] A method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film comprises the following steps:

[0010] S1. PET substrate cleaning: The cut PET is ultrasonically treated with acetone and anhydrous ethanol to remove organic matter and other impurities on the surface of the substrate, the PET is transferred to deionized water, ultrasonicated again, and then dried, and the dried PET substrate is stored;

[0011] S2, PEDOT:PSS solution adjustment: adding the first enhancing liquid to the PEDOT:PSS stock solution to improve the conductivity of the PEDOT:PSS film; using the second enhancing liquid to improve the interface contact between the PEDOT:PSS and the PET flexible substrate;

[0012] S3, spin coating PEDOT:PSS: drop a drop of anhydrous ethanol on the cleaned glass, then slowly cover the PET substrate with the drop to the liquid adsorption film substrate and then spin coat;

[0013] S4, annealing: taking out the spin-coated PEDOT:PSS seed layer, placing it in a vacuum drying oven for annealing, and obtaining a PEDOT:PSS film;

[0014] S5. Pre-sputtering of target material: Turn on the power of water cooling machine, close the gas regulating valve and the air release valve, turn on the vacuum pump switch, make the vacuum degree drop below 2Pa, turn the knob gas regulating valve to stabilize to about 4Pa, and keep it for 5 minutes to fill the cavity with argon gas; turn on the DC power supply for sputtering;

[0015] S6. Sputtering Cu film on PEDOT:PSS / PET substrate: After pre-sputtering, move the sample to the sputtering position, adjust the spacing, set the sputtering power and sputtering time, and perform sputtering. After stopping sputtering, close the gas regulating valve and the vacuum pump handle in sequence, rotate the exhaust valve counterclockwise, and then take out the sample; after sputtering, transfer it to a drying oven for drying;

[0016] S7. Preparation of copper mesh composite conductive film: Import the mesh pattern to be directly written into the nanosecond pulse laser, set the parameters, place the film, and adjust the focal length, then start direct writing to obtain the CuMesh / PEDOT:PSS composite transparent conductive film.

[0017] In one or more embodiments of the present invention, the first enhancement liquid includes ethylene glycol, and the ethylene glycol used in step S2 is added to the PEDOT:PSS stock solution in an amount of 5% by volume.

[0018] In one or more embodiments of the present invention, the second enhancement liquid includes isopropyl alcohol.

[0019] In one or more embodiments of the present invention, the second synergistic liquid in step S2 is diluted with isopropanol as a diluent, and the dilution ratio is 2:1.

[0020] In one or more embodiments of the present invention, the specific step S3 includes:

[0021] S31, placing the glass covered with the substrate in the center of the spin coater suction cup and closing the cover;

[0022] S32, adjust the spin coater to a spin coating speed of 700-900 rpm and a spin coating time of 30-75 s, and start the spin coater to gradually drip the PEDOT:PSS solution onto the PET substrate from the dripping port above.

[0023] In one or more embodiments of the present invention, in step S4, the film is placed in a vacuum drying oven, the temperature is set at 120-180° C. for annealing, and the annealing time is set at 8-20 min to obtain a PEDOT:PSS film.

[0024] In one or more embodiments of the present invention, in the step S5, the sputtering power is 300-500 W, and the sputtering time is 1.5-3.5 min.

[0025] In one or more embodiments of the present invention, in the step S6, during sputtering, the distance between the target and the substrate is adjusted to 9-11 cm, the sputtering power is 80-120 W, and the sputtering time is 1-5 min.

[0026] In one or more embodiments of the present invention, in the step S7, the laser energy density is 1.94-3.88 J / cm2, the scanning speed is 200-600 mm / s, and the direct writing is completed to obtain a CuMesh / PEDOT:PSS composite transparent conductive film.

[0027] Compared with the prior art, the method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film of the present invention has the following advantages:

[0028] 1) In the present application, PEDOT:PSS / PET is used as the substrate instead of PET, and PEDOT:PSS is used as the seed layer, which can not only provide a good wetting effect for the growth of the Cu layer, but also make use of the conductive properties of PEDOT:PSS itself to make the Cu layer and PEDOT:PSS layer composite to exert better photoelectric properties.

[0029] 2) The entire process of this application is simple, does not require complicated operations, has a fast laser direct writing speed, has high pattern flexibility, can adjust pattern parameters at will without being restricted by masks, and has a low preparation cost.

[0030] 3) The present application adopts the spin coating method to prepare the film, which is simple and easy to control parameters. During the spin coating, the centrifugal force evenly distributes the solution on the substrate to form a uniform and smooth film. It can be mass-produced with high repeatability.

[0031] 4) The magnetron sputtering film structure used in this application is more compact and has a strong bonding force with the substrate, making it less likely to crack or peel off. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 This is a preparation flow chart of a method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film in one embodiment of the present invention; DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0035] like Figure 1 As shown, a method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film in one embodiment of the present invention comprises the following steps:

[0036] The following materials were prepared: PET film (thickness 50 μm), PEDOT:PSS (OE-000), ethylene glycol, isopropyl alcohol, anhydrous ethanol, acetone, deionized water, Cu target with a diameter of 50 mm, and sputtering gas argon.

[0037] S1. PET substrate cleaning: ultrasonically treat the cut PET with acetone for 10 minutes; then continue ultrasonicating with ethanol for 10 minutes to remove organic matter and other impurities on the surface of the substrate. After the ultrasonic treatment in ethanol is completed, transfer the PET to deionized water and continue ultrasonicating for 5 minutes. Finally, transfer the PET substrate to a blast drying oven for drying. The dried PET substrate is stored in a glass desiccator;

[0038] S2, PEDOT:PSS solution adjustment: adding the first enhancing liquid to the PEDOT:PSS stock solution to improve the conductivity of the PEDOT:PSS film; using the second enhancing liquid to improve the interface contact between the PEDOT:PSS and the PET flexible substrate, thereby increasing the adhesion and ensuring the reliability and stability of the film;

[0039] The first enhancement liquid includes ethylene glycol, and the ethylene glycol used in step S2 is added to the PEDOT:PSS stock solution in a volume fraction of 5%.

[0040] The second synergistic liquid includes isopropanol. The second synergistic liquid in step S2 is diluted with isopropanol as a diluent at a dilution ratio of 2:1.

[0041] Specifically, the conductivity of the original PEDOT:PSS solution is poor, so the PEDOT:PSS solution was adjusted, and the optimal ethylene glycol addition amount of 5vol% was found through experiments, which can significantly improve the conductivity of PEDOT:PSS; as well as the optimal diluent and dilution ratio, that is, PEDOT:PSS original solution: isopropanol = 2:1, to improve the interface contact with the PET flexible substrate and increase the adhesion

[0042] S3, spin coating PEDOT:PSS: drop a drop of anhydrous ethanol on the cleaned glass, then slowly cover the PET substrate with the drop along one side, use the surface tension between the liquid and the film to tightly adsorb the film substrate and then spin coat;

[0043] S31, placing the glass covered with the substrate in the center of the spin coater suction cup, and closing the device cover;

[0044] S32, select a spin coating process, adjust the spin coater to a spin coating speed of 700-900 rpm, a spin coating time of 30-75 s, and start the process, and gradually drip the PEDOT:PSS solution onto the PET substrate from the dripping port above.

[0045] Preferably, the spin coating speed is 800 rpm, the spin coating time is 45 s, and the spin coater is started to gradually drip the PEDOT:PSS solution onto the PET substrate from the dripping port above. Spin coating is a key step to achieve uniform film thickness. The selection of a spin coating speed of 800 rpm and a spin coating time of 45 s ensures uniform coverage of PEDOT:PSS on the PET substrate, and obtains a uniform and high-performance PEDOT:PSS film.

[0046] S4, annealing: taking out the spin-coated PEDOT:PSS seed layer, placing it in a vacuum drying oven for annealing, and obtaining a PEDOT:PSS film;

[0047] Further, the film is placed in a vacuum drying oven, the temperature is set at 120-180° C. for annealing, and the annealing time is set at 8-20 min to obtain a PEDOT:PSS film.

[0048] Preferably, the temperature in the vacuum drying oven is set at 150°C for annealing, and the annealing time is set to 10 minutes. After the PEDOT:PSS is spin-coated, it is usually necessary to perform annealing to improve its conductivity and stability. The PEDOT:PSS substrate obtained by annealing at 150°C for 15 minutes has excellent performance. This is because the higher annealing temperature improves the crystallinity of the PEDOT molecules and the interaction between the molecules, and increases the electron transport performance of the film.

[0049] S5. Pre-sputtering of target material: Turn on the power of water cooling machine, close the gas regulating valve and the venting valve, turn on the vacuum pump switch, make the vacuum degree drop below 2Pa, turn the knob gas regulating valve to stabilize to about 4Pa, and keep it for 5 minutes to fill the cavity with argon gas; turn on the DC power supply for sputtering, the sputtering power is 300-500W, and the sputtering time is 1.5-3.5min;

[0050] Preferably, the sputtering power is 400 W and the sputtering time is 3 min.

[0051] S6. Sputtering Cu film on PEDOT:PSS / PET substrate: After pre-sputtering, move the sample to the sputtering position for sputtering. Adjust the distance between the target and the substrate to 9-11 cm, the sputtering power to 80-120 W, and the sputtering time to 1-5 min. The sputtering operation steps are similar to those in S5. After the sputtering work stops, close the gas regulating valve and the vacuum pump handle in turn, rotate the vent valve counterclockwise, and then take out the sample. After sputtering, transfer it to a drying oven for drying.

[0052] Preferably, the distance between the target and the substrate is 10 cm, the sputtering power is 100 W, and the sputtering time is 2 min.

[0053] S7. Preparation of copper mesh composite conductive film: Import the mesh pattern drawn by CAD (with a regular hexagonal shape, a spacing of 300 μm, and a line width of 30 μm) into the nanosecond pulse laser, use the software tool provided by the laser to fill the mesh, set the parameters, and then save the mesh graphic as a vlf format file and open it in the working software. Place the film to be directly written on the two-axis workbench, then adjust the focal length of the laser, and start direct writing until the CuMesh / PEDOT:PSS composite transparent conductive film is obtained.

[0054] Furthermore, during direct writing, the laser energy density of the nanosecond pulse laser is adjusted to 1.94-3.88 J / cm2, and the scanning speed is 200-600 mm / s. After the direct writing is completed, a CuMesh / PEDOT:PSS composite transparent conductive film is obtained.

[0055] Preferably, the laser energy density is 2.91 J / cm2 and the scanning speed is 400 mm / s. After the direct writing is completed, the CuMesh / PEDOT:PSS composite transparent conductive film is obtained. The FoM index of the CuMesh / PEDOT:PSS composite transparent conductive film prepared under the process of laser energy density of 2.91 J / cm2 and scanning speed of 400 mm / s reaches a maximum of 414.6. At this time, the transmittance of the composite film reaches 85.8%, and the square resistance is only 5.7Ω / sq.

[0056] In this application, PEDOT:PSS / PET is used instead of PET as the substrate, and PEDOT:PSS is used as the seed layer, which can not only provide a good wetting effect for the growth of the Cu layer, but also, with the help of the conductive properties of PEDOT:PSS itself, the Cu layer and the PEDOT:PSS layer can be combined to exert better photoelectric properties.

[0057] The whole process of the present application is simple, without complicated operation, the laser direct writing speed is fast, the pattern flexibility is high, the pattern parameters can be adjusted at will without being restricted by the mask, and the preparation cost is low.

[0058] The spin coating method used in this application is relatively simple and easy to control parameters. During spin coating, the centrifugal force evenly distributes the solution on the substrate to form a uniform and smooth film. This uniformity is difficult to achieve by many other methods, especially at low thickness.

[0059] The magnetron sputtering film structure used in the present application is more compact and has a strong bonding force with the substrate, and is not prone to cracking or peeling.

[0060] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0061] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film, characterized in that: The steps include: S1. PET substrate cleaning: The cut PET is ultrasonically treated with acetone and anhydrous ethanol to remove organic matter and other impurities on the surface of the substrate, the PET is transferred to deionized water, ultrasonicated again, and then dried, and the dried PET substrate is stored; S2, PEDOT:PSS solution adjustment: adding the first enhancing liquid to the PEDOT:PSS stock solution to improve the conductivity of the PEDOT:PSS film; using the second enhancing liquid to improve the interface contact between the PEDOT:PSS and the PET flexible substrate; S3, spin coating PEDOT:PSS: drop a drop of anhydrous ethanol on the cleaned glass, then slowly cover the PET substrate with the drop to the liquid adsorption film substrate and then spin coat; S4, annealing: taking out the spin-coated PEDOT:PSS seed layer, placing it in a vacuum drying oven for annealing, and obtaining a PEDOT:PSS film; S5. Pre-sputtering of target material: Turn on the power of water cooling machine, close the gas regulating valve and the air release valve, turn on the vacuum pump switch, make the vacuum degree drop below 2Pa, turn the knob gas regulating valve to stabilize to about 4Pa, and keep it for 5 minutes to make the cavity filled with argon gas, turn on the DC power supply for pre-sputtering; S6. Sputtering a Cu film on a PEDOT:PSS / PET substrate: After pre-sputtering, move the sample to the sputtering position, adjust the spacing, set the sputtering power and sputtering time, and perform sputtering. After stopping sputtering, close the gas regulating valve and the vacuum pump handle in sequence, rotate the exhaust valve counterclockwise, and then take out the sample; After sputtering, transfer to a drying oven for drying; S7. Preparation of copper mesh composite conductive film: Import the mesh pattern to be directly written into the nanosecond pulse laser, set the parameters, place the film and adjust the focal length, and then start direct writing to obtain the CuMesh / PEDOT:PSS composite transparent conductive film.

2. The method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film according to claim 1, characterized in that: The first enhancement liquid includes ethylene glycol. The ethylene glycol used in step S2 is added to the PEDOT:PSS stock solution in a volume fraction of 5%.

3. The method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film according to claim 2, characterized in that: The second enhancement liquid includes isopropyl alcohol.

4. The method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film according to claim 3, characterized in that: The second synergistic liquid in step S2 is diluted with isopropanol as a diluent, and the dilution ratio is 2:

1.

5. The method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film according to claim 1 or 3, characterized in that: The specific steps of S3 include: S31, placing the glass covered with the substrate in the center of the spin coater suction cup and closing the cover; S32, adjust the spin coater to a spin coating speed of 700-900 rpm and a spin coating time of 30-75 s, and start the spin coater to gradually drip the PEDOT:PSS solution onto the PET substrate from the dripping port above.

6. The method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film according to claim 5, characterized in that: In the step S4, the film is placed in a vacuum drying oven, the temperature is set at 120-180° C. for annealing, and the annealing time is set at 8-20 min to obtain a PEDOT:PSS film.

7. The method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film according to claim 5, characterized in that: In the step S4, the sample is placed in a vacuum drying oven and annealed at 150° C. for 10 min.

8. The method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film according to claim 7, characterized in that: In the step S5, the sputtering power is 300-500 W, and the sputtering time is 1.5-3.5 min.

9. The method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film according to claim 8, characterized in that: In the step S6, during sputtering, the distance between the target and the substrate is adjusted to 9-11 cm, the sputtering power is 80-120 W, and the sputtering time is 1-5 min.

10. The method for preparing a PEDOT:PSS composite copper grid flexible transparent conductive film according to claim 9, characterized in that: In the step S7, the laser energy density is 1.94-3.88 J / cm2, the scanning speed is 200-600 mm / s, and the direct writing is completed to obtain a CuMesh / PEDOT:PSS composite transparent conductive film.

Citation Information

Patent Citations

  • Plastic-based high-conductivity PEDOT: PSSS film electrode, preparation method and application thereof

    CN104934540A

  • High-conductivity PEDOT: PSS film and preparation method thereof

    CN116693908A

  • Metal grid flexible transparent conductive film and preparation method and application thereof

    CN117558488A

  • Forming method of conductive polymer pattern including acid treatment

    KR101928666B1

  • Electrically Conductive Polymers

    US20100307791A1